CRTH2 expression on T cells in asthma. - Mutalithas, K; Guillen, C; Day, C; Brightling, C; Pavord, I; Wardlaw, A (2010)
Mast cell-derived prostaglandin D2 (PGD2) is the major prostanoid found within the airway of asthmatics immediately following allergen challenge. PGD2 has been shown to have chemokinetic effects on eosinophils and T helper type 2 (Th2) cells in vitro. This occurs through the interaction of PGD2 with the G-protein-coupled chemokine receptor homologous molecule expressed on Th2 lymphocytes (CRTH2). The expression of CRTH2 has been shown to be highly selective for Th2 cells. Using flow cytometry we have studied the expression of CRTH2 on T cells in blood and bronchoalveolar lavage fluid in asthmatics and normal subjects. CRTH2 expression was confined to a small percentage of blood T cells in asthmatics (1.8%+/-0.2) and normal (1.6%+/-0.2) subjects. CRTH2 was enriched significantly on interleukin (IL)-4+/IL-13+ T cells compared to interferon (IFN)-gamma+ T cells (P<0.001). There was a small population of CRTH2+ T cells in the bronchoalveolar lavage (BAL) of asthmatics (2.3%+/-0.6) and normal subjects (0.3%+/-0.1), and there was a significant difference between the two groups (P<0.05). There were similar amounts of PGD2 in the BAL of asthma and normal subjects. Within paired blood-BAL samples from the same subject there was no increase in CRTH2+ T cells in the BAL compared to blood in asthmatics. Enrichment of CRTH2 on IL-4+ and IL-13+ T cells compared to IFN-gamma+ T cells was also seen in BAL from asthmatics (P<0.001). CRTH2 is expressed preferentially by IL-4+/IL-13+ T cells compared to IFN-gamma+ T cells. However, given their small numbers they are unlikely to have a significant involvement in the pathogenesis of asthma. CRTH2 antagonism may not diminish T cell accumulation in the asthmatic lung.